Genome-Wide Association Study of Pericarp Color in Rice Using Different Germplasm and Phenotyping Methods Reveals Different Genetic Architectures - Yang, Wu; Chen, Luo; Zhao, Junliang; Wang, Jian; Li, Wenhui; Yang, Tifeng; Dong, Jingfang; Ma, Yamei; Zhou, Lian; Chen, Jiansong; Wu, Wei; Zhang, Shaohong; et al. (Frontiers in Plant Science, 2022)
Pericarp colors (PC) in rice are determined by the types and content of flavonoid in pericarp. The flavonoid compounds have strong antioxidant activities and are beneficial to human health. However, the genetic basis of PC in rice is still not well understood. Here, a genome-wide association study (GWAS) of PC was performed in a diverse rice collection consisting of 442 accessions using different phenotyping methods in two locations over two years. In the whole population consisting of white and colored pericarp rice, a total of eleven QTLs were identified using two phenotyping methods. Among these QTLs, nine were identified using the phenotypes represented by presence and absence of pigmentation in pericarp, while ten were identified using phenotypes of degree of pericarp color (DPC), in which eight are common QTLs identified using the two phenotyping methods. Using colored rice accessions and phenotyped based on DPC, four QTLs were identified and they are totally different from the QTLs identified using the whole population, suggesting the masking effects of major genes on minor genes. Comparing with the previous studies, ten out of the fifteen QTLs are first reported in the present study. Based on the differential expression analysis of the predicted genes within QTL region by both RNA-seq and RT-PCR, and the gene functions in previous studies, LOC_Os01g49830, encoding a RAV transcription factor was considered as the candidate gene underlying qPC-1, a novel QTL with large effect in the present study. Our results provide the new insight in the genetic basis of pericarp color in rice, and contribute to develop the value-added rice with optimized flavonoid content through molecular breeding.